Improving psychosocial and digital care pathways for Duchenne muscular dystrophy: insights from the Duchenne Switzerland Conference 2025 (Swiss Medical Weekly, 2026)
Duchenne muscular dystrophy (DMD) is a rare neuromuscular disease, affecting approximately 1 in 3,500 to 5,000 live male births worldwide. Despite medical advances, families continue to face considerable challenges in navigating fragmented health and social care systems, coping with long-term uncertainty, and accessing timely psychosocial and digital support.This viewpoint summarises key themes, identifies knowledge transfer strategies, and proposes future directions for optimising DMD care in Switzerland and internationally. It reflects the growing recognition that successful care for rare diseases such as DMD must centre families and follow a holistic approach that combines excellent clinical care with digital innovation and psychosocial support frameworks.Our conclusions are drawn from the Duchenne Switzerland Conference 2025, held on 26 September at the Swiss Paraplegic Centre in Nottwil, Switzerland, a unique forum for interdisciplinary exchange between families, clinicians, therapists, researchers, and patient organisations involved in the care and support of individuals with DMD. With over 120 participants and a fully multilingual setup, the conference highlighted current care challenges, psychosocial needs across the DMD care continuum, and emerging digital health solutions.The programme included keynote lectures and parallel sessions covering topics such as digital platforms and patient journey tools, assistive technologies, participation and empowerment, mental health, care management, and community-based care. Evidence from international and national research projects, including data from the Care-NMD-CH project, underscored regional disparities and systemic gaps in service provision. The role of coordinated care networks such as Myosuisse and Swiss-Reg-NMD was also discussed in the context of citizen science and participatory research and care approaches.Workshops and presentations showcased examples of inclusive technologies and participatory health communication, including AI-assisted translation and digital tools to enhance daily autonomy and engagement for individuals with DMD. Sessions on mental health and resilience highlighted the ongoing emotional and psychological strain on families, emphasising the need for sustainable psychosocial interventions as part of integrated care.